2008
DOI: 10.1007/s00423-008-0395-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct hemoperfusion with polymyxin-B-immobilized fiber columns improves septic hypotension and reduces inflammatory mediators in septic patients with colorectal perforation

Abstract: Our findings suggested that PMX treatment appears to adsorb endotoxin and also modulates circulating cytokine during a 2-h interval of direct hemoperfusion in septic patients with such condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 42 publications
1
16
1
1
Order By: Relevance
“…Our results were similar to the findings of previous studies [10,11,12], which showed that survivors commenced PMX earlier after the onset of shock than patients who died. In patients with severe sepsis or septic shock, early administration of appropriate antibiotics, corticosteroids, and recombinant human activated protein C are all associated with better survival [13].…”
Section: Discussionsupporting
confidence: 83%
“…Our results were similar to the findings of previous studies [10,11,12], which showed that survivors commenced PMX earlier after the onset of shock than patients who died. In patients with severe sepsis or septic shock, early administration of appropriate antibiotics, corticosteroids, and recombinant human activated protein C are all associated with better survival [13].…”
Section: Discussionsupporting
confidence: 83%
“…The authors hypothesized that the delay in initiation of therapy had an impact on survival. Comparable results were seen in patients with colorectal sepsis [29] and septic multiorgan failure [16]. …”
Section: Refining the Treatment Strategy: Time-to-initiation Of Pmxmentioning
confidence: 70%
“…However, whether PMX-DHP removes cytokines remains controversial [8,28]. A recent multicenter study on PMX-DHP reports the adsorption of endotoxin and also the modulation of circulating cytokines in septic patients [29].…”
Section: Discussionmentioning
confidence: 99%